Challenges Experienced by Youth Organizations during the Ratification of Bangsamoro Organic Law - Laniel Ryan Untong; Princess Sheryn Mamucao; Nor Ann Abdilla; Marsharita Kasim (RIRAI Publisher, 2022)
Acknowledging the role of the youth in nation building as stated in the Republic Act also known as Youth in Nation-Building Act in the Philippines, youth organizations take part in the ratification of the Bangsamoro Organic Law for the Bangsamoro people in the said country. However, various challenges have been faced. This study aimed to determine the challenges these youth organizations have experienced during their participation in the law’s ratification. It also sought to identify the coping mechanisms they have employed to cope with those challenges during the ratification of the Bangsamoro Organic Law. To determine the challenges faced and coping mechanisms of the youth organizations, a qualitative type of research was used, and data was presented in narrative form. The participants which were selected purposely were officers of Al-Jalis As-Salih, Inc. (AAI); United Youth for Peace and Development (UNYPAD); Ittihadun – Nisa Foundation (INFO); Bangsamoro Youth Project Organization (BYPO); Young Centrist Union (YCU); and United Youth of the Philippines – Women (UNYPHIL). Purposive sampling was used in selecting the participants. The study found out that the youth organizations faced series of challenges during the ratification of the Bangsamoro Organic Law such as receiving threat and having a hard time convincing people to vote for “YES” which means agreeing for the law’s ratification. The youth also faced challenges during the posting of materials in Cotabato City, Philippines since the City Mayor is not in favor of the Bangsamoro Organic Law which led to various heated situations. Other challenges experienced are related to local traditional politics, different dynamics within the ground, differences of religion, capacity and resources of organization, financial concerns, the misinterpretation and misconception and myths on Bangsamoro Organic Law. It is then concluded that despite the challenges faced by the youth, they maximized their utmost participation and did not give up. Their steadfastness in achieving their goal is what made them tough to counter the waves of challenges.